Inquiring children and elementary school teachers to diagnose their conceptions about islands - Vasconcelos, Clara; Paz, Marta (Frontiers in Education, 2023)
Current challenges faced by modern societies assign larger importance to geological knowledge, particularly in the youngest, as geoscience education is an important path towards a more comprehensive understanding of the Earth’s processes and, therefore, to achieve a more sustainable world. The present investigation aims to deepen knowledge regarding the conceptions related to islands and islands’ formation. Children’s diagrams and drawings are prototypical representations of how they view and understand their world and can also illustrate misunderstandings in their knowledge. This article studies the conceptions of islands in elementary school children (K-9) and elementary school teachers. For that purpose, the investigation resorted to a small survey based on a drawing task. The sample consisted of 118 elementary school students (n=118), whose ages ranged from six to ten years old, and their four elementary school teachers (n= 4), whose ages ranged from 43 to 49 years old. In line with prior studies, that acknowledged the existence of many misconceptions regarding geology topics, this investigation found unscientific ideas about islands, both in students and teachers. The results of the study show that students and teachers share misconceptions about the formation of islands and their relation with the seafloor. The implications of our findings for science education are discussed, namely the development of an Earth sciences education for elementary schooling and the construction of educational resources better adapted to the teaching and learning of the topic.